2017
DOI: 10.1093/jpepsy/jsx059
|View full text |Cite
|
Sign up to set email alerts
|

Young Children’s Acute Stress After a Burn Injury: Disentangling the Role of Injury Severity and Parental Acute Stress

Abstract: Our findings confirm mothers' crucial role in the posttraumatic adjustment of young children. Clinically, mothers' acute stress should be monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…The second sample included 154 children aged 1–4 years ( M age = 2.71 years, SD = 0.07; 63.6% male) who were medically treated at the University Children's Hospital Zurich (Zurich, Switzerland) in the aftermath of burn injury (Haag & Landolt, ). The sample was part of a randomized controlled trial (RCT) testing the effectiveness of an early psychological intervention for preschool children and their parents following accidental burn injury (De Young, Haag, Kenardy, Kimble, & Landolt, ).…”
Section: Methodsmentioning
confidence: 99%
“…The second sample included 154 children aged 1–4 years ( M age = 2.71 years, SD = 0.07; 63.6% male) who were medically treated at the University Children's Hospital Zurich (Zurich, Switzerland) in the aftermath of burn injury (Haag & Landolt, ). The sample was part of a randomized controlled trial (RCT) testing the effectiveness of an early psychological intervention for preschool children and their parents following accidental burn injury (De Young, Haag, Kenardy, Kimble, & Landolt, ).…”
Section: Methodsmentioning
confidence: 99%
“…While most previous research has studied the effects of camp on the children with burn injuries themselves, it is acknowledged that adult family members are also dealing with the trauma and can exhibit clinically significant levels of psychosocial distress following the injury (Haag & Landolt, 2017). Siblings are also affected, often experiencing a number of difficulties relating to the burn, such as the teasing of their brother or sister by others, and feeling excluded or ignored while parents/carers focus on their injured sibling (Phillips, Fussell, & Rumsey, 2007).…”
mentioning
confidence: 99%
“…Another possible explanation is the low injury severity in the current study. While injury severity is not a good predictor of PTSS, some studies have reported significant associations (i.e., Haag & Landolt, 2017), which may have influenced the low rates of PTSS. Furthermore the small sample size might have made it difficult to detect PTSD, which is already understood to be a small percentage of the population.…”
Section: Discussionmentioning
confidence: 98%
“…Children are particularly watchful for information from parents regarding situational safety during a traumatic event (Hornik & Gunnar, 1988;van der Kolk, 1987). Regarding pediatric injury, young children appear to react to their injury severity indirectly through their mother's (but not father's) psychological distress reactions (Haag & Landolt, 2017). Two studies have investigated maternal sensitivity during immunizations for infants and toddlers (Din, Pillai Riddell, & Gordner, 2009;Pillai Riddell et al, 2011).…”
Section: Parental Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation